Bulgarian Constructions with the Apprehensive Particle da ne bi in the Bulgarian National Corpus - Иванова, Елена Ю. (Języki słowiańskie dziś: w kręgu kategorii, struktur i procesów, 2021)
This article is devoted to semantic and grammatical properties of sentences with the Bulgarian particle da ne bi. Based on the Bulgarian National Corpus (8,400 contexts), the study outlines structural-semantic types of dependent and independent clauses with the particle da ne bi and their qualitative representation in the Corpus. It also defines conditions for the apprehensive interpretation of sentences with da ne bi. The analysis provides evidence in support of the assumption that the particle da ne bi should be isolated out of the entity da ne bi da, commonly treated as an integrated conjunction/particle, and shows grammatical consequences of the use of this particle for sentence structure.